2016
DOI: 10.4103/2231-0762.197200
|View full text |Cite
|
Sign up to set email alerts
|

Urban and rural disparity in tobacco use and knowledge about oral cancer among adolescents: An epidemiological survey on 12 and 15-year school going students

Abstract: Aims and Objectives:To assess and compare the tobacco use prevalence; to understand and compare attitudes and knowledge related to tobacco use and its health impact among urban and rural students; and to assess urban and rural disparity in the use of tobacco among 12 and 15-year-old adolescents in the urban and rural schools in Chhattisgarh, India.Materials and Methods:A cross-sectional study was conducted among 12 and 15-year-old and urban and rural school going children in Durg District. Scientifically, base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Previous studies reported significant urban-rural difference for tobacco consumption and the rate was higher among rural compared with urban children, similar to our study. 30 The BMI of school children is significantly differed between urban and rural area was also justified by an Indian study of Punjab. 31 Again, two other studies reported same difference in dietary pattern among urban and rural children.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies reported significant urban-rural difference for tobacco consumption and the rate was higher among rural compared with urban children, similar to our study. 30 The BMI of school children is significantly differed between urban and rural area was also justified by an Indian study of Punjab. 31 Again, two other studies reported same difference in dietary pattern among urban and rural children.…”
Section: Discussionmentioning
confidence: 97%
“…These findings may be partly attributed to the smoking norms in China, in which smoking is overwhelmingly a male phenomenon 19 . Higher exposure in suburb school students may be attributed to differences in tobacco prevalence 21 and environment due to weak implementation of smokefree policies in suburb areas 22 . Our finding targeting vocational school students could be explained by their special learning and living environment; they directly enter into the workforce after graduation and are more likely to encounter social smokers 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Lifestyle, socioeconomic differences such as education and income, low access to preventive health care services such as cholesterol screening, cardiac rehabilitation and a routine physical checkup [ 2 , 35 ].The distribution of common MI risk factors (obesity, smoking) and mortality rate were considerably high at rural areas compared to urban areas in USA. The smoking and obesity rates in US rural are 29.6 and 39.6% compared to 24.2 and 33.4% in the urban USA population respectively [ 36 , 37 ]. A higher AAIRMI in rural areas may be attributed to the difference in quality of life and lifestyle factors between rural and urban communities or it may arise from systematic differences between rural and urban cultures [ 38 ].…”
Section: Discussionmentioning
confidence: 99%